Rewriting : how to do things with texts - Harris, Joseph (Joseph D.) (Published by Utah State University Press, an imprint of University Press of Colorado, 2017)
"Harris draws the college writing student away from static ideas of thesis, support, and structure, and toward a more mature and dynamic understanding and to think of intellectual writing as an adaptive and social activity, with a clear set of strategies--a set of moves--for participating"--Provided by publisher